A prospective randomized study of the efficacy of "Turning Point, " an inpatient violence intervention program. Issue 5 (November 2016) - Loveland-Jones, Catherine; Ferrer, Lucas; Charles, Scott; Ramsey, Frederick; van Zandt, Andrea; Volgraf, Jill; Santora, Thomas; Pathak, Abhijit; Dujon, Jay; Sjoholm, Lars; Rappold, Joseph; Goldberg, Amy
Abstract : BACKGROUND: From 2002 to 2011, there were more than 17, 000 shootings in Philadelphia. "Turning Point, " Temple University Hospital's inpatient violence intervention program, takes advantage of the teachable moment that occurs after violent injury. In addition to receiving traditional social work services, Turning Point patients watch their trauma bay resuscitation video and a movie about violence, meet with a gunshot wound survivor and an outpatient case manager, and also undergo psychiatric assessment. The purpose of this study was to determine the efficacy of Turning Point in changing attitudes toward guns and violence among victims of penetrating trauma. METHODS: This prospective randomized study was conducted from January 2012 to January 2014. Patients who sustained a gunshot or stab wound were randomized to standard of care, which involved traditional social work services only, or Turning Point. The Attitudes Toward Guns and Violence Questionnaire was administered to assess attitude change. Analysis was performed with repeated-measures analysis of variance. A p < 0.05 was significant. RESULTS: A total of 80 of a potential 829 patients completed the study (40 standard of care, 40 Turning Point). The most common reason for exclusion was anticipated length of stay being less than 48 hours. The two groups were similar with respect to most demographics. Unlike the standard-of-care group, the Turning Point group demonstrated a 50% reduction in aggressive response to shame, a 29% reduction in comfort with aggression, and a 19% reduction in overall proclivity toward violence. CONCLUSIONS: Turning Point is effective in changing attitudes toward guns and violence among victims of penetrating trauma. Longer follow-up is necessary to determine if this program can truly be a turning point in patients' lives. LEVEL OF EVIDENCE: Therapeutic/care management study, level II.